Viral Infections and Febrile Seizures - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2005)
The incidence of febrile seizures (FS) in a cohort of children, ages 3 months to 5 years, living in a Netherlands province was compared with the incidence of common viral infections reported to a national registry and the results reported from the Department of Medical Microbiology, Public Health Laboratory Friesland, Leeuwarden, The Netherlands.